Pengaruh Kepercayaan Pelanggan Dan Citra Perusahaan Terhadap Loyalitas Pelanggan Pada Bagian Pergudangan PT Agung - Kartikaningsih, Dewi; Surip, Surip; Simanjuntak, Robby; Sumarsid, Sumarsid; Gunardi, Gunardi (Jurnal Sekretaris dan Administrasi Bisnis, 2023)
PT Agung Raya is one of the companies engaged in shipping services (logistiks) that always chooses accurate strategies to always gain customer trust, maintain the company's image and of course be able to make it continue to survive in the midst of the onslaught of similar companies. The data version which used in this study is primary data, namely data obtained directly from respondents, through data collection techniques using questionnaires or questionnaires, which are filled out by respondents. The object of research in this study is the warehousing department of PT Agung Raya with the research sample being customers of the warehousing department of PT Agung Raya. The findings in this stuy indicate that there is a positive influence of customer trust on customer loyalty where the significance value was 0.006 <0.05 and the coefficient value was 0.217. There is a positive and significant effect of corporate image on customer loyalty, the significance value is 0.000 <0.05 and the coefficient value is 0.375. And there is a positive and significant influence on customer trust, company image on customer loyalty, with a significance value of 0.000 <0.05 and a coefficient value of 123.672. The effect of customer trust, company image on customer loyalty is 76.8%.